Insights into PLGA-encapsulated epigallocatechin 3-gallate nanoparticles as a new potential biomedical system: A computational and experimental approach. (3rd January 2023) - Minnelli, Cristina; Stipa, Pierluigi; Sabbatini, Simona; Mengucci, Paolo; Mobbili, Giovanna; Galeazzi, Roberta; Armeni, Tatiana; Romaldi, Brenda; Celli, Annamaria; Laudadio, Emiliano
Graphical abstract: Highlights: The polymer nanoparticles with EGCG are spherical with a uniform size distribution. Infra-Red spectra shows that PLGA is able to correctly encapsulate EGCG. The interactions between PLGA and EGCG avoid polyphenols' aggregates. The nanoparticles exhibit promising cytotoxic potentials in human A549 cell lines. Abstract: Biodegradable poly-lactic poly-glycolic copolymer (PLGA) represents one of the best strategies adopted to convey small molecules unstable and characterised by a low bioavailability if administered without vehicles. This is the case of Epigallocatechin-3-gallate (EGCG), which is one of the most interesting polyphenols from a biomedical point of view. In this study, the impact of EGCG on PLGA nanoparticles (NPs) properties has been studied underlining the role of the binary PVA/Poloxamer-407 as stabilizer system for obtaining colloidal stable NPs. Characterization has been carried out by dynamic light scattering (DLS), encapsulation efficiency, drug release studies, scanning electron microscopy (SEM) and infrared spectroscopy (IR). Molecular dynamics (MD) simulations have been used to model the PLGA and EGCG systems to understand the behaviour of NPs and the interactions that guided the EGCG encapsulation. The nanodispersions exhibited promising cytotoxic potentials in human lung carcinoma A549 cell lines enhancing the well-known growth inhibitor effect of the free EGCG.